Ensino de física e atividades em grupo: um estudo de caso em mecânica - Oliveira, Maico Stoichicov Borges (2019)
Based on a didactic sequence, covering mechanics, consisting of 11 classes in a regular classroom and 2 classes in an extra period, the present work seeks to obtain greater interest from students for a physics discipline. With investigative and group experimental activities, a greater attitudinal development of the students towards the formulation of physical concepts is sought, and with it, to develop a more meaningful learning.The sequence was developed in a class of 1st year of High School, with 10 students from a private school. After the end of the work, a good improvement was observed in the students’ behavior towards the discipline, where they were more questioning and always sought to relate the studied contents. It is also worth noting that some students remained disinterested and hardly improved.